Analisis Kesalahan Siswa dalam Menyelesaikan Soal Sistem Persamaan Linier Dua Variabel (SPLDV) Ditinjau Dari Gaya Belajar Siswa SMP (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
The purpose of this study is to find out the error done by junior level students in solving two-variable linear equations system in terms of their learning styles. This type of research is a qualitative descriptive research. The data collection technique used was a questionnaire, written tests, interviews and documentation. The subjects of this study were 3 students of SMP Negeri 2 Karangtengah. Each of them has with a visual learning style, auditory learning style, or kinesthetic learning style. The validity of the data is done by technical triangulation. Data analysis were done using the data reduction, data presentation, and drawing conclusions. The results of the research are (1) students with a visual learning style make mistakes at the stages of making plans, implementing plans and re-examining solutions; (2) students with an auditory learning style make mistakes at the planning stage; (3) students with a kinesthetic style make mistakes at the stage of carrying out the plan and re-examining the solution.
Keywords: Error Analysis; Two Variables Linear Equation System